Studies of Cadmium Selenide (CdSe) Nanoparticles Synthesized by Solvo-thermal Route - Krishna ratnam3 and Chidambaradhanu4, S. Ganapathy Raman1, P. Selvarajan2* (Recent Research in Science and Technology, 2010)
Synthesis of nanoparticles of Cadmium Selenide(CdSe) was carried out by using a microwave oven. Cadmium chloride and sodium selenite were used as the precursor materials to prepare CdSe nanoparticles. Ethylene glycol was used as the capping agent to control the size of the nanoparticles. Powder XRD pattern reveals the crystal structure of the prepared CdSe nanoparticles. The average particle size of the sample was found to be 54 nm. The morphology of the sample was studied by a SEM. UV-vis absorption spectrum for prepared CdSe sample was recorded. Dielectric studies were carried out for the pelltized sample of CdSe nanoparticles and AC conductivity and DC conductivity values have been measured. The obtained results are discussed.